ELECTROCHEMICAL NOISE TECHNIQUE IN MONITORING C02 CORROSION IN HIGH PRESSURE AND HIGH TEMPERATURE ENVIRONMENT - KHAIRULANNUAR, IZZUDIN (2013)
Electrochemical Noise (EN) is considered as a convincing technique in monitoring CO2 corrosion as it offers less complexity of setup and instrumentation, and it is practical to be utilized at particular field. It also produces better accuracy in reading as it needs no external polarization which influences the electrochemical reaction. Other conventional techniques require more complex setup; usage of three (3) different electrodes, whereas EN offers simpler and more robust setup to monitor CO2 corrosion. Moreover, identifying localized corrosion and pitting is crucial because it is one of the most damaging forms of corrosion as it is more difficult to detect, predict, design against and can lead to an unexpected catastrophic system failure. Furthermore, partial protective film breakdown is always associated with high pressure and high temperature (HPHT) environment and EN has an advantage in discriminating between different types of corrosion processes.